EFFECT OF SHADING ON HALF-CUT SOLAR PANELS POWER OUTPUT - Pratama, Bayu Angga; Hiendro, Ayong; Marpaung, Jannus; Yusuf, M. Ismail; Imansyah, Fitri (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
The output power generated by the photovoltaic module and its lifetime depend on many aspects. Some of these factors include: type of PV material, intensity of received solar radiation, cell temperature, parasitic resistance, clouds and other shadowing effects, inverter efficiency, dust, module orientation, weather conditions, geographical location and cable thickness and others. There are several environmental parameters that can affect the performance of solar cells, including changes in temperature, intensity of solar radiation, partial covering of the surface of the solar cell. Partial covering of the solar cell surface is usually caused by dust adhering to the solar panel for a certain period of time or it can also be caused by animal droppings such as birds that accidentally hit and cover the surface of the solar panel. Because it causes the closing of the solar cell, the performance of the solar cell will not be maximized, so it can greatly affect the decrease in the value of the output power and also the current generated. But how big the resulting influence is not yet known. The data logger managed to record the necessary parameters of the PV circuit that is applied to the shadow, namely, Voc voltage, working voltage, working current and power. The application of a rectangular shadow pattern has differences from a circle pattern, namely: in a rectangular pattern: a significant voltage drop occurs when the shadow is applied by 60%, the PV can still emit current although it is relatively small, the PV no longer emits voltage when the shadow is more than 70% , whereas in the circle pattern: the PV voltage starts to drop after the shadow is applied by 30%, if the shadow is more than 30% then the PV is no longer flowing current.